Septic shock due to Candida famata (Debaryomyces hansenii) candidemia in an ICU immunocompetent trauma-patient. Issue 4 (July 2019) - Karapetsa, Maria; Tsolaki, Vasiliki; Arabatzis, Michael; Petinaki, Efi; Velegraki, Aristea; Zakynthinos, Epaminondas
Abstract: Sepsis related to Candida famata (C. famata) fungemia is extremely rare in immunocompetent patients. Moreover, septic shock has not been reported due to this yeast. A previously healthy young multi-trauma male, presented septic shock from C. famata, after he had been admitted in the Intensive Care Unit (ICU) due to haemorrhagic shock. Risk factors for candidemia in ICU patients are the presence of a central venous catheter (CVC), Total Parenteral Nutrition (TPN), use of broad-spectrum antimicrobials, immunosuppression and the length of ICU stay. The presence of CVCs, prior use of antibiotics, prolonged hospitalization, disruption of skin flora and immunocompromised states have been identified as predisposing risk factors for C. famata fungemia. It is worth noting that the present case concerns a non-immunocompromised patient, but long ICU stay and brain injury may indicate a state of immunoparalysis. Identification of the yeast was performed by partial amplification and sequencing of the 26S ribosomal DNA gene [hypervariable region D1/D2; partial sequencing of the act1 gene confirmed the identity of the strain as Debaryomyces hansenii (GenBank submission ID: 1688297)] The patient quickly recovered from sepsis after initiation of amphotericin B and was discharged on the 60th day.